1993
DOI: 10.1111/j.1365-2958.1993.tb01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variation of pilin regulates adhesion of Neisseria meningitidis to human epithelial cells

Abstract: Pili have been shown to play an essential role in the adhesion of Neisseria meningitidis to epithelial cells. However, among piliated strains, both inter- and intrastrain variability exist with respect to their degree of adhesion to epithelial cells in vitro (Virji et al., 1992). This suggests that factors other than the presence of pili per se are involved in this process. The N. meningitidis pilin subunit undergoes extensive antigenic variation. Piliated low- and high-adhesive derivatives of the same N. meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
244
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(247 citation statements)
references
References 29 publications
3
244
0
Order By: Relevance
“…The strain used in this study is a derivative of the piliated, Opa 2 , Opc 2 , PilC1 + and PilC2 + serogroup C N. meningitidis 8013 strain (Nassif et al, 1993). N. meningitidis strains were grown on GC agar (GCB; Difco), supplemented with Kellogg's defined supplement (Kellogg et al, 1963) overnight at 37 uC in a moist atmosphere containing 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The strain used in this study is a derivative of the piliated, Opa 2 , Opc 2 , PilC1 + and PilC2 + serogroup C N. meningitidis 8013 strain (Nassif et al, 1993). N. meningitidis strains were grown on GC agar (GCB; Difco), supplemented with Kellogg's defined supplement (Kellogg et al, 1963) overnight at 37 uC in a moist atmosphere containing 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, receptor specificity of the sialic acid E. coli adhesin SfaS appears to be variable depending on the fimbrial subunit with which it is associated (31). Studies in pathogenic neisseria species have suggested a role for the pilin subunit PilE in epithelial cell interaction because changes in its primary structure arising via antigenic variation have been reported to influence adherence proficiencies and tissue tropism (12,(14)(15)(16). Given their structural identities in the amino terminal domains thought to be crucial to subunit-subunit contact, one explanation might relate to the differing capacities of altered PilE protein and PilV to interact productively with one another, leading to reduced or defective PilV activity.…”
Section: Pilc and Pilv Content In Pilus Preparations From Adherence-dmentioning
confidence: 99%
“…However, several studies have suggested a role for the pilin subunit PilE in receptor recognition. These include numerous findings showing that different antigenic variant forms of PilE influence epithelial cell adherence and tissue tropism (12,(14)(15)(16). However, the structural and functional attributes of PilE accounting for these observations remain unknown.…”
mentioning
confidence: 99%
“…Z5463 is a naturally transformable serogroup A strain that belongs to the same sequence type as strain Z2491 (Sarkari et al, 1994). N. meningitidis 8013 (2C4.3), a serogroup C strain (C : 22 : NST : L3,7,9), was also used in this study (Nassif et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Z5463(SB-aph39) was obtained following transformation of DNA of strain N. meningitidis 8013 SB-aph39 mutant (kanamycin resistant) (Nassif et al, 1993) into Z5463. Both strains Z5463orf6-aph39 and Z5463orf6 : : aph39 were constructed by an overlapping method using the oligonucleotides listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%